A Typological and Morphological Analysis of the Pleurothallidinae (Orchidaceae) Inflorescences - Rojas Alvarado, Gustavo (2024)
Despite its relevance, the study of the inflorescence from a typological point of view generally goes unnoticed in taxonomy, which is fundamental for the comparison of structural elements of the same origin. Pleurothallidinae is not the exception, and its typology has not been studied in detail, causing incorrect interpretations of its structures and misapplication of terms. Here the morphology of Pleurothallidinae inflorescences is analyzed and discussed from a typological point of view, based on the detailed study of structural elements of living material, which are illustrated by photographs and diagrams. The study shows that the subtribe presents a generalized type of inflorescences formed by an abbreviated peduncle and branch system that cannot be seen with the naked eye. Each branch may produce coflorescences of different lengths with one or multiple flowers, also presenting different patterns of succession that determine the general appearance of the plant. Single-flowered coflorescences are dominant in members of the Octomeria and Restrepia affinities, while multi-flowered coflorescences dominate the Acianthera, Lepanthes, Masdevallia, Phloeophila, Pleurothallis and Specklinia affinities. A general and practical classification is established for the different types of coflorescences according to the length and number of flowers produced.